ABOUT ONE METHOD OF CONTROLLING THE PARAMETERS OF A GIVEN POLYLINE - Suvankulov Ilkhomjon Shakhobiddinovich (Journals Park Publishing, 2025)
An iterative algorithm of the static-geometric method of forming a broken line with equal angles of adjacent links and pairwise equal links is considered.
Keywords: modeling, broken, structure, system, iteration.